2002
DOI: 10.1200/jco.2002.08.674
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab as First-Line and Maintenance Therapy for Patients With Indolent Non-Hodgkin’s Lymphoma

Abstract: Rituximab is highly active and extremely well tolerated as first-line single-agent therapy for indolent NHL. First-line treatment with scheduled maintenance at 6-month intervals produces high overall and complete response rates and a longer progression-free survival (34 months) than has been reported with a standard 4-week treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
247
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(260 citation statements)
references
References 14 publications
8
247
1
3
Order By: Relevance
“…Rituximab alone was also studied in patients with a more aggressive presentation, needing treatment at diagnosis or after some follow-up without treatment (Hainsworth et al, 2002). The RR, just after four infusions, was comparable with the one observed in relapsing patients (50% and less than 10% of CR).…”
Section: Rituximab In Flmentioning
confidence: 92%
“…Rituximab alone was also studied in patients with a more aggressive presentation, needing treatment at diagnosis or after some follow-up without treatment (Hainsworth et al, 2002). The RR, just after four infusions, was comparable with the one observed in relapsing patients (50% and less than 10% of CR).…”
Section: Rituximab In Flmentioning
confidence: 92%
“…This combines antibodies that specifically target antigens selectively expressed on tumour cells and cytotoxic effector mechanisms. Successful clinical use includes the treatment of breast cancer by HER-2-specific trastuzumab (Goldenberg, 1999), follicular non-Hodgkin B-cell lymphoma by CD20 specific rituximab (Hainsworth, 2000).…”
mentioning
confidence: 99%
“…Current studies have shown that a prolonged exposure to rituximab after the end of the primary treatment may reduce relapse rate and improve event-free survival in patients with FL and MCL [13][14][15]. In follicular lymphoma, rituximab maintenance therapy is now part of the standard of care in relapsed disease [10,15].…”
Section: Discussionmentioning
confidence: 99%
“…Hochster et al [12] reported a significant prolongation of response duration and even survival by R maintenance in patients with previously untreated advanced-stage FL responding to initial therapy without R comprising chemotherapy by cyclophosphamide, vincristine, and prednisone (CVP) alone. In former investigations, Hainsworth et al [13] and Ghielmini et al [14] already had found that R maintenance was beneficial when given to patients with FL who achieved a partial remission or complete remission after initial singleagent first-line R therapy. In a recent publication, R maintenance after R chemotherapy was investigated in patients with recurring or refractory FL and MCL.…”
Section: Introductionmentioning
confidence: 99%